In – vitro study of Allium schoenoprasum L. leaf crude extracts against Curvularia lunata, causal agent of brown leaf spot disease in rice / Nur Aina Ishak - Ishak, Nur Aina (Faculty of Plantation and Agrotechnology, 2019)
Rice plays an important role as a wage community for workers either in the cash crops or non-agriculture sectors. Besides that, it also has feed more people around the world over a longer period of time. However, the production and the quality of rice become decrease due to infection from disease. Brown leaf spot caused by fungus Curvularia lunata is one of the disease that give problem in the rice production and quality. There are several ways to control the population of brown leaf spot and one of the alternative methods is biological control. Biological control of the plant pathogens by using plant extracts is one of the potential non chemical methods in managing the plant disease. The purpose of this study was to determine the effectiveness of Allium schoenoprasum L (chives) against C. lunata with different concentration of the leaf crude extract. The experiment was conducted by using the poison food technique and different concentration (10%, 20% and 40%) of leaves extract were mixed well together. Highest growth inhibition was achieved by 40% concentration of Allium schoenoprasum L at 42.78% mycelia growth inhibition. Extract of leaf crude of Allium schoenoprasum L at 40% concentration promoted significant (P≤0.00) inhibition on mycelia growth of C. lunata compared to the control. Thus, it could be inferred that leaf extract of Allium schoenoprasum L at 40% concentration can be serve as bio-fungicide against the growth of C. lunata.